Analisis Peran Himpunan Serikat Perempuan Indonesia Deli Serdang dalam Meminimalisir KDRT Sebagai Upaya Menurunkan Angka Perceraian di Deli Serdang - Fadilah, Irfandi; Lubis, Azwani (Universitas Ekasakti, 2023)
This study aims to find out the mapping of problems and solutions faced by the Deli Serdang Indonesian Women's Union Association, in an effort to help clients overcome problems that cause divorce. second, to how find out the counseling implementation strategy carried out by the Deli Serdang Indonesian Women's Union Association in overcoming the problem of divorce. This research is an empirical research or field research. The approach used in this study is a qualitative approach. Methods of data collection is done by means of interviews, observation and documentation. The data analysis method used is descriptive qualitative data analysis. The results of this study indicate that: 1) Problems causing divorce that were consulted at HAPSARI Deli Serdang, including: presence of a third person (PIL/WIL), failure to communicate, social media, hyper sex, polygamy, and non-fulfillment of husband's or wife's rights . And the solutions given include giving advice, giving motivation, giving directions for self-introspection, having the nature of openness, paying attention to partners to maintain harmony in the household, and giving fatwas for issues related to Islamic law unless there is something that allows it. 2) The strategy carried out at HAPSARI Deli Serdang is to pay attention to the principles of counseling that are applied including principles based on service objectives, principles based on individual problems, principles based on service programs, principles of service implementation. The strategies used are listening and seeing, describing problems, providing views, advising, providing alternative solutions, providing directions, providing motivation, independence, digging for other information, and providing solutions based on the Qur'an and sunnah.